Optimization of Ultrasonic Extraction of Total Flavonoids from Cinnamonum zeylaniccum - Seyma Balcı; Sibel Yiğitarslan (International Journal of Secondary Metabolite)
Cancer is the most widespread disease in the world currently. The availability of using controlled-drug-releasing capsules for those cancer diseases had become more and more important. The initial operation of the production process of the capsules requires the extraction of the active ingredients from the plant. Phytochemicals exert positive effects on human health and thus they are important compounds found in medicinal plants like Cinnamonum zeylaniccum. Flavonoids are the most effective phytochemicals having more than four thousand different types and they are well known antioxidants especially used in treatments of cancer diseases. In the light of these information, the aim of this study was to optimize the ultrasonic extraction of flavonoids (as a raw-material fort he capsules) from Cinnamonum zeylaniccum with methanol by using Response Surface Methodology. Batch extraction experiments had been carried out with the parameters of solid-to-liquid ratio, extraction temperature and time, by applying ultrasounds on sweep mode. Multi-parameter optimization was carried out with three-parameter, three-level, three-centered Box-Behnken design considering the optimum values obtained in single-parameter optimization. Design-Expert software was used to obtain the function representing the extraction yield surface depending on the selected parameters. As a result of the statistical analysis, the function expressing the effect of the parameters on the resulting amount of quercetin production in industry had been derived as reduced cubic model. Solid-to-liquid ratio was found as the most effective parameter on the extraction yield. At the optimum conditions (30°C, 1/10 g/ml, and 15 minutes), 12.34 mg quercetin equivalent total flavonoids were extracted.